Using association rules analysis to determine favorable mineralization sites in the Jiaojia gold belt, Jiaodong Peninsula, East China - Mao, Xiancheng; Tang, Miao; Deng, Hao; Chen, Jin; Liu, Zhankun; Wang, Jinli (Frontiers in Earth Science, 2023)
Mesozoic orogenic gold deposits in the Jiaojia goldfield, Eastern China show the features of regular mineralization spatial distribution and have long been captivated the attention of geologists. This study integrates 3D modeling, model space analysis, and association rule analysis to extract the relationship between structural deformation and gold mineralization. The Apriori algorithm with spatial constraints is used to quantify the favorable mineralization sites in the Jiaojia gold field using different combinations of ore-controlling indicators. The first favorable mineralization site has a 44% probability of mineralization and is primarily located in segments of the fault footwall within 25 m of the fault buffer where the transition from steep to gentle occurs (∼1–24). Its uniform distribution indicates that the ore-bearing space near the main fault plane is relatively wide, and hydrothermal diffusion is relatively uniform. Site No. 2 has a 45% probability of mineralization and is located in convex segments (6–35 m) between 25 and 55 m of the fault footwall. The equidistant zonal distribution in this area indicates that secondary faults and fractures have facilitated the migration of hydrothermal fluids, resulting in the formation of extensive ore-bearing spaces. Site No. 3 sited in convex segments (∼0–6 m) distal to the fault footwall (∼55–515 m) of the fault buffer where the dip is gentle (∼30°–35°). The binary structure of differing dips formed by the intersection of steeply dipping orebodies and the slowly dipping orebodies in the central and southern parts of the Nanlü-Xinmu deposit exhibit the complex channel away from the main fault. In this study, the correlation between ore-controlling factors and mineralization in Jiaojia fold field is quantitatively expressed as favorable mineralization sites in the form of association rules, it would contribute to a deeper understanding of the underlying mechanisms governing the formation of structure-controlled orogenic gold deposits in the Jiaojia goldfield.